Electrical Conductivity in Ba5RTi3-xZrxNb7O30 [R = La or Dy] Ceramics - SINGH, N.K. (Asian Journal of Chemistry, 2010)
The polycrystalline samples of Ba5RTi3_xZrxNb7O30 [R = La or Dy; x = 0, 1,2,3] belonging to tungsten-bronze (TB) structural family were prepared by using conventional high-temperature solid-state reaction technique. Studies of electrical conductivity/resistivity as a function of biasing electrical field and a wide range of temperature have been carried out. The activation energy (Ea) of the compounds was calculated from the plot of dc resistivity and ac conductivity vs. absolute temperature. Dc resistivity studies show that the increase of Zr concentration enhances the resistivity characteristics of Ba5DyTi3 _ xZr xNb7O30 and decreases the resistivity characterisities of Ba5LaTi3 _ xZrxNb7O30 compounds. The compounds exhibit the negative temperature coefficient of resistance (NTCR) properties at higher temperature region.